THE INVESTIGATION OF THE RELATIONSHIP BETWEEN SOCIAL VULNERABILITY AND SELF-ESTEEM OF UNIVERSITY STUDENTS (Third Sector Social Economic Review, 2018)
AbstractUniversity life is a period when young people face change and on the other hand they have to cope with personal development and social pressure. For this reason, there are many psychological, cultural and environmental factors that affect young people's self-esteem. One of these factors is social vulnerability. The sample of the study consists of 400 students studying at Hacettepe University in 2016 - 2017 academic year and volunteering to participate in the research. Data were collected with Coopersmith Self-Esteem Inventory, Social Vulnerability Scale and demographic information form. According to the findings, 76.3% of the students were female and 23.7% of the students were male. The average age of the students is 20 (S = 1.6). Among the students, the percentage of residents in the dormitory (70.0%) is high. Correlation analysis displayed that there is a significant negative correlation at 0.01 level (r = -. 310, p
Keywords: University students; self-esttem; vulnerability; socail vulnerability; social vulnerability of students